2018
DOI: 10.1016/j.marpolbul.2018.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and contamination assessment of heavy metals in marine sediments of the southern coast of Sfax, Gabes Gulf, Tunisia

Abstract: In order to investigate the current distribution of metal concentrations in surface marine sediments of the southern coast of Sfax (Tunisia), thirty-nine samples were collected in the vicinity of a mixed industrial and domestic wastewater effluent discharge. In comparison with the threshold effect level and probable effect level, the majority of metals had high ecological and biological risks. Enrichment factor and geoaccumulation Index showed that the majority of sediments are unpolluted by As, Ni and Pb, mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 56 publications
(48 reference statements)
1
30
0
1
Order By: Relevance
“…Our results demonstrated that resuspension of surface contaminated sediment from the Sfax coast led to high releases of Cd, U and V in seawater. High concentrations of Cd were initially found in surface sediment collected in front of mixed wastewater discharge into the seawater (El Hakmouni Wadi), as detected in previous studies on surface sediments of the Sfax southern coast (Zouch et al, 2017; Naifar et al, 2018). The fate and distribution of As, Cd, U and V are driven by complex processes controlled by abiotic and biotic parameters.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Our results demonstrated that resuspension of surface contaminated sediment from the Sfax coast led to high releases of Cd, U and V in seawater. High concentrations of Cd were initially found in surface sediment collected in front of mixed wastewater discharge into the seawater (El Hakmouni Wadi), as detected in previous studies on surface sediments of the Sfax southern coast (Zouch et al, 2017; Naifar et al, 2018). The fate and distribution of As, Cd, U and V are driven by complex processes controlled by abiotic and biotic parameters.…”
Section: Discussionmentioning
confidence: 52%
“…For several decades, many industrial complexes have settled on the coast of the Gulf of Gabès (GG), a shallow gulf located in the southern Mediterranean Sea. These coastal industrial expansions, coupled with urban growth, have enhanced marine pollution, mainly due to the discharge of urban/industrial effluents into seawater, which has led to a high diversity of contaminants, including metals (Ayadi et al, 2015; Zaghden et al, 2016; El Zrelli et al, 2018; Naifar et al, 2018). The long-term discharge of phosphogypsum (i.e., a by-product of the phosphate fertilizer industries having acidic pH and containing trace metals) and/or untreated acidic wastewaters in the GG has resulted in a progressive degradation and loss of biodiversity, which represent a real threat for the marine ecosystems (El Zrelli et al, 2017; El Kateb et al, 2018; Naifar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classification and characterization of PGs based on current legislations are not well known due to the fact that most studies on PG have focused on the environmental impact of this waste on the surrounding landfilling area, but not on the possible species leaching. Published studies, in Tunisia, have focused mainly on the spatial characterization of pollution near PG storage areas, by mapping the concentration levels of chemical elements and specifying contaminated areas [23,25,26]. But, no clear results on the quantification of released pollutants (trace elements, heavy metals,…) contained in Tunisian PGs.…”
Section: Introductionmentioning
confidence: 99%
“…Esta contaminação pode impactar o ambiente aquático produzindo componentes poluentes que podem entrar na cadeia alimentar humana e ocasionar problemas de saúde (EREGNO et al, 2018). De fato, a contaminação metálica em ambientes aquáticos tem recebido grande preocupação devido a sua toxicidade (NAIFAR et al, 2018).…”
Section: Degradação Ambientalunclassified